Functional characterization of the Thr946Ala SNP at the type 1 diabetes IFIH1 locus. (February 2014) - Zouk, Hana; Marchand, Luc; Li, Quan; Polychronakos, Constantin
Abstract The Thr allele at the Thr946Ala non-synonymous single-nucleotide polymorphism (nsSNP) in the IFIH1 gene confers risk for type 1 diabetes (T1D). IFIH1 binds viral double-stranded RNA (dsRNA), inducing a type I interferon (IFN) response. Reports of this nsSNP's role in IFIH1 expression regulation have produced conflicting results and a study evaluating transfected Thr946Ala protein alleles in an artificial system overexpressing IFIH1 shows that the SNP does not affect IFH1 function. In this study, we examine the effects of the Thr946Ala polymorphism on IFN-α response in a cell line that endogenously expresses physiological levels of IFIH1. Eleven lymphoblastoid cell lines (LCLs) homozygous for the major predisposing allele (Thr/Thr) and 6 LCLs homozygous for the minor protective allele (Ala/Ala) were electroporated with the viral dsRNA mimic, poly I:C, in three independent experiments. Media were collected 24 hours later and measured for IFN-α production by ELISA. Basal IFN response is minimal in mock-transfected cells from both genotypes and increases by about 8-fold in cells treated with poly I:C. LCLs with the Ala/Ala genotype have slightly higher IFN-α levels than their Thr/Thr counterparts but this did not reach statistical significance because of the large variability of the IFN response, due mostly to two high outliers (biological, not technical). A larger sample size would be needed to determine whether the Thr946Ala SNP affects the poly I:C-driven IFN-α response. Additionally, the possibility that this nsSNP recognizes viral dsRNA specificities cannot be ruled out. Thus, the mechanism of the observed association of this SNP with T1D remains to be determined.